2018
DOI: 10.1101/358168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced repertoire of cortical microstates and neuronal ensembles in medically-induced loss of consciousness

Abstract: SUMMARYMedically-induced loss of consciousness (mLOC) has been linked to a macroscale break-down of brain connectivity, yet the neural microcircuit correlates of mLOC remain unknown. We applied non-linear t-stochastic neighbor embedding (t-SNE) and Lempel-Ziv-Welch complexity analysis to two-photon calcium imaging and local field potential (LFP) measurements of cortical microcircuit activity across anesthetic depth in mice, and to micro-electrode array recordings in human subjects.We find that mLOC disrupts po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…It has been shown that LZc decreases concomitantly with the loss of phenomenological possibilities, which is consistent with theoretical views of consciousness (Tononi & Edelman, 1998). Lempel-Ziv complexity algorithm computes the number of non-redundant segments of a signal (Lempel & Ziv, 1976), which in turn, when applied to brain data, is related to the abundance of the repertoire of brain activity patterns observed (Wenzel et al, 2019). During the transition from wakefulness to sleep or anesthesia, the number of possible experiences and cognitive processes that one can have is greatly reduced.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…It has been shown that LZc decreases concomitantly with the loss of phenomenological possibilities, which is consistent with theoretical views of consciousness (Tononi & Edelman, 1998). Lempel-Ziv complexity algorithm computes the number of non-redundant segments of a signal (Lempel & Ziv, 1976), which in turn, when applied to brain data, is related to the abundance of the repertoire of brain activity patterns observed (Wenzel et al, 2019). During the transition from wakefulness to sleep or anesthesia, the number of possible experiences and cognitive processes that one can have is greatly reduced.…”
Section: Introductionsupporting
confidence: 71%
“…The slope of the spectral power law has been linked to E/I balance (Lombardi et al, 2017), while LZc reflects the vastness of the repertoire of brain activity patterns (Wenzel et al, 2019). Although these two measures may seem unrelated at first, we hypothesize that both reflect a specific type of entropy of cortical systems.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Theoretical work has demonstrated that ND can serve as a proxy for integrated information in highly recurrent systems where integration can be assumed, such as the brain (Marshall et al, 2016). Consistent with IIT's predictions, several studies have employed differentiation analysis across a range of species and spatiotemporal scales to show that loss of ND is implicated in loss of consciousness (Casali et al, 2013;Hudetz et al, 2014;Barttfeld et al, 2015;Wenzel et al, 2019).…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, our data indicate that supercritical networks cause increased population covariance which reduces the number of metastable states. Given the evidence for reduced brain state diversity during a loss of awareness induced by general anaesthesia (Schartner et al, 2015;Wenzel et al, 2019), we hypothesise that impaired metastability may explain the loss of awareness that occurs during generalised seizures (Blumenfeld & Taylor, 2003). In this way, supercritical networks may give rise to brain dysfunction in epilepsy.…”
Section: Understanding Epileptic Seizures Through the Lens Of Critical Systemsmentioning
confidence: 96%